Social cognitive impact of essential tremor - Sarah Melchert; Oliver L. Steiner; Christin Kupper; Hannah Lochmann; Michelle Wyrobnik; Fabian Klostermann (Scientific Reports)
Abstract Though classified as a movement disorder, essential tremor (ET) goes along with minor cognitive change. This mainly refers to executive functions, thought to be of paramount importance for social cognition, particularly cognitive theory of mind (ToM). Therefore, different ToM and executive tasks were assessed in persons with versus without essential tremor. 21 non-demented patients with essential tremor and 29 healthy controls underwent cognitive screening, different tasks addressing executive functions, and the faux pas recognition test (FPRT) as well as the reading the mind in the eye test (RMET), focusing on cognitive and affective ToM, respectively. Patients performed significantly worse than controls in the verbal fluency and the digit span tests as well as in the FPRT. No significant group differences were identified with respect to RMET performance. The results are compatible with the idea that persons with ET develop subtle cognitive ToM deficits in the context of executive dysfunction. This extends descriptions of the non-motor impact of ET by deficits in social cognition and raises the question whether potential cognitive change of affected patients is sufficiently acknowledged in clinical routine.